Propagation of gravity waves and spread F in the low-latitude ionosphere over Tucumán, Argentina, by continuous Doppler sounding: first results - Chum, J. (2014)
Results of systematic analysis of propagation directions and horizontal velocities of gravity waves (GWs) and spread F structures in low-latitude ionosphere (magnetic inclination ~27°) in Tucumán region, Argentina, are presented. Measurements were carried out by multipoint continuous Doppler system during 1 year from December 2012 to November 2013. It was found that meridian propagation of GWs dominated and that southward propagation prevailed in the local summer. Oblique spread structures observed in Doppler shift spectrograms and associated with spread F propagated roughly eastward at velocities from ~70 to ~180 m/s and were observed at night from ~ September to ~ March. The velocities were computed for 182 events and the azimuths for 64 events. Continuous Doppler sounding makes it possible to analyze more events compared to optical observations often used for propagation studies since the measurements do not depend on weather.